Determinants of Islamic stock market / Nur Annisa Muhammad Ridha Djamily - Muhammad Ridha Djamily, Nur Annisa (Faculty of Business Management, 2014)
This research will focus on the relationship between strategic commodities (oil and gold prices), industrial production index, consumer price index, exchange rate and financial aggregate supply and the Islamic stock market in Malaysia. The objective of this research is to identify the factors that affect the Islamic stock market (FBMES) crude oil prices (COP), gold prices (GP), industrial production index (IPI), financial aggregate supply (M3), consumer price index (CPI) and exchange rate (MYR). Therefore, the relationship between Islamic stock market and COP, GP, IPI, M3, CPI and MYR will be found through this research. There are six variables that will be involved in this research. The dependent variable is Islamic stock prices (FBMES). The independent variables are crude oil prices (COP), gold prices (GP), industrial production index (IPI), financial aggregate supply (M3), consumer price index (CPI) and exchange rate (MYR). This research will use Ordinary Lease Square Method (OLS) to examine the effect of each variable on Islamic stock market and it will be regressed by using e-views software. Data was collected from January 2008 to December 2012. This finding will contribute to investors whether worth it or not in investing Islamic stock market to avoid losses.